The Phenolic Composition of South African Pinotage, Shiraz and Cabernet Sauvignon Wines - Rossouw, M.; Marais, J. (South African Journal of Enology and Viticulture, 2017)
Phenolic compounds are major constituents of red wines and impact on certain wine-quality parameters. This study has aimed to increase the knowledge base on the phenolic composition of South African red wines by HPLC quantification of 39 individual phenols and 2 polymeric, phenolic groups in 260 South African wines of the cultivars Pinotage, Shiraz and Cabernet Sauvignon. Statistical analysis of the collected data revealed significant cultivar differences in the levels of many of the analysed compounds, as well as in the ratios in which specific anthocyanins are found in the wines. These data may be helpful in the cultivar authentication of wines of these cultivars. Discriminant analysis of the data showed statistically significant separations of cultivars, based on their polyphenol composition, and also how the use of data from a specific wine-producing area or vintage improved the possibilities for successful authentication. The data were collected from both pure cultivar wines and commercial wines, which may contain up to 15 % of another cultivar wine. The collected data may therefore be further segmented into those obtained from pure cultivar wines and those obtained from blended wines in order to further enhance the accuracy of authentication of these respective groups of wines. The information obtained from this study opens several avenues for research on the impact of the noted cultivar differences on wine quality. Cultivar differences in the phenolic composition of young red wines also have important implications for the oenological management of oxidation reactions taking place during vinification and aging.